Gendered opportunities and constraints in milk trading in peri-urban Nairobi - Galiè, Alessandra; Myers, Emily (International Livestock Research Institute, 2018)
Presented by Alessandra Galie (ILRI) and Emily Myers (IFPRI), as part of a webinar organized by ILRI and the CGIAR Research Program on Agriculture, Nutrition and Health (A4NH), hosted by the CGIAR Collaborative Platform for Gender Research. The webinar took place on December 17, 2018.